T-X corpus [data set] - Radich, Michael (Zenodo, CERN, 2022)
This corpus includes the Taishō and Xuzangjing/Zokuzōkyō collections of Chinese Buddhist texts, as digitised by CBETA, processed so that they are ready for use with the text-analysis tool TACL or the TACL GUI.